1971
DOI: 10.1073/pnas.68.6.1316
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Contact-Inhibited Growth to Transformed Cells by Dibutyryl Adenosine 3′:5′-Cyclic Monophosphate

Abstract: Spontaneously transformed and virallytransformed cells are restored to contact-inhibited growth by the addition of dibutyryl cyclic AMP to the nutrient medium. Theophylline, an inhibitor of the phosphodiesterase that degrades cyclic nucleotides, must also be present for maximal effect. Once the transformed cells reach a saturation density in the presence of the additives, release from the contact-inhibited state occurs upon removal of the dibutyryl cyclic AMP and theophylline from the medium. Agglutinability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
2

Year Published

1972
1972
1982
1982

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(52 citation statements)
references
References 31 publications
4
45
1
2
Order By: Relevance
“…The effect of DB-cAMP on the cell proliferation was similar to that in some other cell lines, in which the compound appears to restore the contact-inhibited state of the cells, leading to a reduced saturation density (Teel and Hall, 1973;Sheppard, 1971). However, the present results suggest a similarity between the actions of DB-cAMP and butyrate, implying that DB-cAMP could have acted through degradation to butyrate.…”
Section: Discussioncontrasting
confidence: 55%
“…The effect of DB-cAMP on the cell proliferation was similar to that in some other cell lines, in which the compound appears to restore the contact-inhibited state of the cells, leading to a reduced saturation density (Teel and Hall, 1973;Sheppard, 1971). However, the present results suggest a similarity between the actions of DB-cAMP and butyrate, implying that DB-cAMP could have acted through degradation to butyrate.…”
Section: Discussioncontrasting
confidence: 55%
“…In the latter, cAMP rose three-to four-fold when cells reached confluency and growth ceased (15). Exogenous cAMP or agents that raised intracellular levels of cAMP restored contact inhibition and several normal morphologic characteristics to transformed cells (2)(3)(4)14). Similarly, cAMP has been shown to inhibit lymphocyte mitogenesis have lower cAMP levels during the S and M phases of their growth cycle than during G1 and G2 (35,36).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been suggested that some of the abnormal properties of transformed cells are related to alterations in cAMP metabolism (33). In keeping with this possibility, transformed cells treated with agents that elevate cAMP levels lose some of the properties of the transformed cell phenotype (15,16,31,39,43).…”
mentioning
confidence: 87%